DETERMINANTS OF THE PERCEIVED INTERNSHIP EFFECTIVENESS: EXPLORING STUDENTS’ EXPERIENCES - IVANA, Diana (Studia Universitatis Babeș-Bolyai Oeconomica, 2019)
Internships are increasingly important for the business higher education as they help students to make the connection between their academic studies and the world of business. This study analyzes the internships of students within an international study program (German line of study) in order to determine what factors account for the most valuable internship experience. Based on the elements of the experiential education approach, the results reveal some characteristics that contribute to a higher level of perceived internship effectiveness in accordance with the employment status and gender. These results provide a basis for designing successful internship programs in business universities. JEL classification: I23, J24